2019
DOI: 10.3389/fcimb.2019.00223
|View full text |Cite
|
Sign up to set email alerts
|

In vitro and in silico Models to Study Mosquito-Borne Flavivirus Neuropathogenesis, Prevention, and Treatment

Abstract: Mosquito-borne flaviviruses can cause disease in the nervous system, resulting in a significant burden of morbidity and mortality. Disease models are necessary to understand neuropathogenesis and identify potential therapeutics and vaccines. Non-human primates have been used extensively but present major challenges. Advances have also been made toward the development of humanized mouse models, but these models still do not fully represent human pathophysiology. Recent developments in stem cell technology and c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
16
0
4

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(20 citation statements)
references
References 246 publications
(305 reference statements)
0
16
0
4
Order By: Relevance
“…To date, around 20 articles ( Table 1 and Table 2 ) have studied USUV growth kinetics using these in vitro systems. This number is very small compared with that of publications dealing with other mosquito-borne flaviviruses, such as WNV (around 110) or with Dengue virus (over 200) [ 70 ], which explains, at least in part, the scarcity of information about USUV infection and control. The USUV prototype strains SAAR-1776 (GenBank: AY453412, Culex neavei), which were isolated by intracerebral inoculation of newborn mice [ 18 ], and Vienna 2001 (GenBank: AY453411, Blackbird) were mainly used in these experiments.…”
Section: In Vitro Modelsmentioning
confidence: 98%
“…To date, around 20 articles ( Table 1 and Table 2 ) have studied USUV growth kinetics using these in vitro systems. This number is very small compared with that of publications dealing with other mosquito-borne flaviviruses, such as WNV (around 110) or with Dengue virus (over 200) [ 70 ], which explains, at least in part, the scarcity of information about USUV infection and control. The USUV prototype strains SAAR-1776 (GenBank: AY453412, Culex neavei), which were isolated by intracerebral inoculation of newborn mice [ 18 ], and Vienna 2001 (GenBank: AY453411, Blackbird) were mainly used in these experiments.…”
Section: In Vitro Modelsmentioning
confidence: 98%
“…Furthermore, Teng et al [ 53 ] observed that ZIKV-related proteins might overlap the microcephaly associated proteins at the P53 signaling pathway, where P53 is the hub of the genetic regulatory network, causing viral-infection-induced cell death, thereby leading to a disorder characterized by abnormal brain development. Recently Chesnut et al [ 54 ] summarized the research on in vitro and in silico models to study mosquito-borne flavivirus neuropathogenesis, prevention and treatment. This review article reporting on an in silico genetic screening approach performed by Kumar et al [ 55 ] was utilized to elucidate that ZIKV-elicited congenital microcephaly may act through dysregulation of the retinoic acid response element (RARE).…”
Section: Discussionmentioning
confidence: 99%
“…Further details pertaining to the correlations between virulence and inner shell disorder among the mentioned viruses can be found in previous papers. 10 , 17 19 , 43 45 The CFRs of the viruses have been well-studied and documented. 46 − 48…”
Section: Introductionmentioning
confidence: 99%
“…As also seen in Figure , the high correlations ( R ) as seen in the coefficients of determination ( R 2 ) of greater than 0.25 for the various viruses reveal strong correlations between virulence and inner shell disorder. Further details pertaining to the correlations between virulence and inner shell disorder among the mentioned viruses can be found in previous papers. , , The CFRs of the viruses have been well-studied and documented.…”
Section: Introductionmentioning
confidence: 99%